2006
DOI: 10.1002/mc.20279
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of p73 and MDM2 polymorphisms on the risk of lung cancer

Abstract: p73, a structural and functional homologue of p53, plays an important role in modulating cell-cycle control and apoptosis. MDM2 represses the transcriptional activity of p73 and thus attenuates its activity. Based on the interaction between p73 and MDM2 in cell-cycle control and apoptosis, we investigated the association between p73 G4C14-to-A4T14 and MDM2 309T > G polymorphisms, alone and in combination, on the risk of lung cancer in a Korean population. The p73 and MDM2 genotypes were determined in 582 lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 31 publications
1
20
1
Order By: Relevance
“…The results revealed that the frequencies of the three genotypes and the allele distributions were significantly different between the NSCLC patients and the healthy controls. In addition, there was a significant difference between the GG and TT genotypes, and subjects carrying the T allele had a significantly decreased risk of developing NSCLC in the current Southern Chinese population compared with that of patients carrying the GG genotype, which was consistent with the results of Jun et al (31). Therefore, these findings further supported the present result that the MDM2 SNP309 T allele may reduce the risk of developing NSCLC.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results revealed that the frequencies of the three genotypes and the allele distributions were significantly different between the NSCLC patients and the healthy controls. In addition, there was a significant difference between the GG and TT genotypes, and subjects carrying the T allele had a significantly decreased risk of developing NSCLC in the current Southern Chinese population compared with that of patients carrying the GG genotype, which was consistent with the results of Jun et al (31). Therefore, these findings further supported the present result that the MDM2 SNP309 T allele may reduce the risk of developing NSCLC.…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that individuals carrying the G allele of MDM2 SNP309 were more sensitized to develop both hereditary and sporadic cancers (22). Various studies have reported an increased risk of developing lung cancer for the carriers of the G allele in Korean and Chinese populations (31,32). Previous studies confirmed that the G allele of MDM2 SNP309 was associated with higher expression levels of MDM2 protein (21).…”
Section: Discussionmentioning
confidence: 94%
“…The flow diagram of included/excluded studies. The included studies were as follows: Alhopuro et al, 2005;Hong et al, 2005;Sotamaa et al, 2005;Boersma et al, 2006;Campbell et al, 2006;Dharel et al, 2006;Hu et al, 2006;Li et al, 2006;Lind et al, 2006;Ma et al, 2006;Ohmiya et al, 2006;Onat et al, 2006;Park et al, 2006;Petenkaya et al, 2006;Pine et al, 2006;Wilkening et al, 2006;Zhang et al, 2006;Alazzouzi et al, 2007;Cox et al, 2007;El Hallani et al, 2007;Hirata et al, 2007;Jun et al, 2007;Meissner Rde et al, 2007;Schmidt et al, 2007;Walsh et al, 2007;Wasielewski et al, 2007;Wilkening et al, 2007a;Yang et al, 2007;Zhou et al, 2007;Asomaning et al, 2008;Cho et al, 2008;Ellis et al, 2008;Horikawa et al, 2008;Kibel et al, 2008;Liu et al, 2008a,b;Mittelstrass et al, 2008;Nakashima et al, 2008;Paulin et al, 2008;Singh et al, 2008;Stoehr et al, 2008;Terry et al, 2008;Tu et al, 2008;…”
Section: And Supplementarymentioning
confidence: 99%
“…Intriguingly, an apparently protective effect of A4T14 was reported in a small study comprising 84 esophageal carcinoma patients and 152 controls in Ireland (Ryan et al 2001). Interestingly, two independent studies performed in Korean populations showed no significant allelic differences for p73 G4C14-to-A4T14 in lung cancer risk Jun et al 2007). Together, these observations suggest that the effects of p73 G4C14-to-A4T14 could be dependent on the ethnic background of the population studied.…”
Section: P21 Codon 31mentioning
confidence: 99%